Penentuan Oil Losses dan Faktor Koreksi Pada Jalur Pipa Pengiriman Minyak Mentah di Sumatera Selatan - Hariyadi H; Edgie Yuda Kaesti (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Crude oil delivery system in South Sumatra by using the same pipes for oil companies raises the problem that is the loss of oil (oil losses) between Gathering Station as a delivery point with Center Production Gathering system. At this time there has been a change in the crude oil shipping operations both in production volume and the number of business partners involved in the delivery of crude oil. Changes in crude oil shipments were caused either by the discovery of petroleum source of new, decreasing oil production, changes in the volume of oil delivered and others resulted in a correction factor of production calculated at an earlier time is not representative anymore and needed re-evaluation.Conducting a study on the factors reevaluation oil losses in some parts of the oil field consisting of several groups (Segment) to determine the correction factor based on the production of oil properties, operating conditions and delivery process are other factors that influence it. The correction factor consists of oil shrinkage,water and sediment, emulsion and evaporation.